La pasión política (Aportes para una ética política post-moderna) - Fernando Mires (Espacio Abierto, 2001)
Sooner or later, sociologists and politicalphilosophers, with few exceptions, end up referringto the theme of the differences between whatis considered truly political, and what is ethicalor moral. This difference however is far from relevant.But it is particularly important in the globaltimes of today, when it is assumed that politicshas been replaced by pure economic reasoning.This would mean that in the global times ofmodernity there are no conflicts, because thereare no real actors, neither social nor political. Inthe face of this catastrophic and resigned mannerof thinking, I have protested before in another publication(Mires, 2000). I wish to refer now to thetheme of the inter-relations between morality,ethics and politics that has not passed beyond asecond level. It has, on the contrary, more validitynow if we wish to recover political reasoning, especiallyin Latin American countries where theprocess of constructing democracy, both formaland real, is far from being over, with or withoutglobalization. The political sociology of the postmodernage which is still in the making, must recoverthe ethical-political legacy from the Athenianera up to the present, with an attempt to understandthe sense and reason of these public placesthat were created so that our conflicts and interestscould be reconciled without recurring toviolence, something that has recently seemed possiblein certain Latin American countries. So-calledcitizen virtues are, effectively, the result oflong historical processes marked by multiplepre-political adventures. Before virtues appearedon the citizen menu, a lot of blood flowed underthe bridges. This paper is an essay that centersfirst on the relationships between ethics, politicsand morality. In the second place, we refer to thetheme of passions, from the point of view of politicalvirtue. Lastly, we refer to a more permanentpolitical theme: truth and non-truth in the life ofthe citizen.